Chronic pain and impaired glial glutamate transporter function in lupus-prone mice are ameliorated by blocking CSF-1 receptors - Yan, Xisheng (J Neurochem, 2017)
Systemic lupus erythematosus (SLE) is a multi-organ disease of unknown etiology in which the normal immune responses are directed against the body’s own healthy tissues. Patients with SLE often suffer from chronic pain. Currently, no animal studies have been reported about the mechanisms underlying pain in SLE. In this study, the development of chronic pain in MRL lupus-prone (MRL/lpr) mice, a well-established lupus mouse model, was characterized for the first time. We found that female MRL/lpr mice developed thermal hyperalgesia at the age of 13 weeks, and mechanical allodynia at the age of 16 weeks. MRL/lpr mice with chronic pain had activation of microglia and astrocytes, over-expression of CSF-1 and IL-1β, as well as suppression of glial glutamate transport function in the spinal cord. Intrathecal injection of either the CSF-1 blocker or IL-1 inhibitor attenuated thermal hyperalgesia in MRL/lpr mice. We provide evidence that the suppressed activity of glial glutamate transporters in the spinal dorsal horn in MRL/lpr mice is caused by activation of the CSF-1 and IL-1β signaling pathways. Our findings suggest that targeting the CSF-1 and IL-1β signaling pathways or the glial glutamate transporter in the spinal cord is an effective approach for the management of chronic pain caused by SLE.